Pak-US Relations under Trump Administration - Musavir Hameed; Saeeda Batool; Muhammad Ibrar Aslam; Zain Ali (ASIAN Journal of International Peace & Security (AJIPS), 2021)
In retrospect, ties between the United States (US) and Pakistan were at their pinnacle during the tenures of Pakistan’s military rulers. When civilian administrations ruled in Islamabad, ties between the two nations remained strained. During the Trump administration, American foreign policy towards Pakistan remained volatile. Relations worsened to a record low during the early years of the Trump administration, but then began to recover in the later years. This research offers insight into the elements that lead to a strained relationship between the US and Pakistan, while Pakistan is being blamed for the political upheaval in Afghanistan. The US holds Pakistan responsible for the continuous problems in Afghanistan and uses the Financial Action Task Force (FATF) as a political platform to put pressure on Pakistan. Furthermore, the US regards China-Pakistan Economic Corridor CPEC as a debttrap tactic by China, Besides, the increasing US ties with India are seen as a threat to Pakistan, with the US administration continuously offering India more space in the Afghan peace process and signing various military pacts primarily to counter rising China, while Pakistan sees it as a threat to its security.